Exploring the professional judgement practises of classroom assessment among primary science teachers - Abu Bakar, Nuraini; Abdul Manaf, Umi Kalthom; Hassan, Aminuddin; Mustakim, Siti Salina (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Classroom assessment is one of the transformations in Malaysia education system. It was emphasised on the students' perspectives, their diversity of learning styles, and intellectual development. A good measure of assessment for learning should have the capacity to track student progress as well as help students recognize areas for improvement (Pat-El, Tillema, Segers & Vedder, 2013). There are important criteria that required by a teacher in implementing classroom assessment, which is known as professional judgement. Professional judgement is a consideration made using professional knowledge of the intended curriculum covers knowledge, skills, values, evidence of achievement, teaching strategies, assessment methods, and criteria and standards. Professional judgement requires teachers to make ethical and responsible decisions about the level of students based on the analysis and summary of information on learning (BPK, 2018). However, findings by Daisy (2013) indicates that teachers have least competency in constructing and appraising classroom assessment. There is another issue when parents have questions about the teachers’ credibility and integrity in doing assessment. They feel hesitant to trust the teacher to assess their children. Besides that, parents are also worried that teachers are biased in assessing their children and feeling less confident about the ability of the teacher to assess their students (Ramlah Ab Khalid & Jamil Ahmad, 2015). Therefore, it is important for teachers to have a genuine professional judgement in order to convince the parents and shows their reliability. Considering the influence of professional judgement on students’ assessment outcomes has lead researcher to explore on teachers ‘practise and confidence towards their professional judgements. This is a qualitative case study. This study involved four science teachers as the respondents. The findings show that there are six factors of teacher’s understanding towards professional judgement; i. Teacher’s daily practise in implementing professional judgement, ii. Teacher’s perception about professional judgement, iii. Teacher’s challenge in implementing professional judgement, iv. Teacher’s incompetency in implementing professional judgement, v. Teacher’s confidence in professional judgement and vi. Suggestion to improve teacher’s professional judgement. The findings should alert teachers to improve their competency in using professional judgement by practicing all the knowledge and skills needed in assessing pupils’ learning. Besides that, the findings on teachers’ perception towards classroom assessment and professional judgement will give feedback to other relevant parties such as Teacher Education Division and Curriculum Development Division to provide appropriate trainings and briefings regarding teachers’ professional judgement to teachers.